Corporate Governance, Intellectual Capital, and Dividend Policy: Impact on Firm Value - Indah Sukmaningsih; Husnah Nur Laela Ermaya (International Journal of Small and Medium Enterprises and Business Sustainability, 2022)
This study empirically examines the effect of corporate governance, intellectual capital, and dividend policy on firm value with the covid-19 pandemic as a control variable on the Kompas 100 index companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This study uses quantitative methods with secondary based on financial statements and annual reports. The sample collected in this study is 39 samples in Kompas 100 index companies using the purposive sampling method. The data analysis techniques used are model specification test, classical assumption test, multiple linear regression, and hypothesis testing using a simultaneous test (f- test) and partial test (t-test) with STATA version 16. The results show that (1) the independent board of commissioners has no effect on firm value, (2) the audit committee has a significant negative effect on firm value, (3) intellectual capital has no effect on firm value, and (4) dividend policy has a significant positive effect on firm value.